PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH (Studi kasus pada nasabah BPR BKK Jepara Cabang Kecamatan Kota) - Adi Candra Agus S, 08.05.51.0118; Farchan, Farchan (Students Journal of Economic and Management, 2012)
Research with the tittle "The Influence of Service Quality and Product Quality Of Customer Satisfaction" done for the purpose to analyze customer satisfaction in Jepara Branch BPR BKK city. The population in this study is BPR BKK Jepara who use services and products provided by the BPR. Sampling was done by using "purposive sampling", ie sampling technique was done on purpose to record the sample representative of the population and the number of samples taken as many as 100 persons / respondents. The data collected was analyzed using: Factor analysis to test the validity of the statement items, Cronbach Alpha formula to test the reliability of the instrument, a regression analysis to examine the degree of influence of each independent variable on the dependent variable then the coefficient of determination and F-test is used to test the goodness of the model (Goodness of Fit). Based on data analysis and hypothesis testing results obtained: (1) that the partial variable service quality has positive and significant impact on customer satisfaction, (2) product quality variables have a positive and significant impact on customerÂ  satisfaction, (3) the variable quality of service and product quality with both positive and significant impact on customer satisfaction. Of the five indicators of service quality variables are physical evidence, reliability, responsiveness, assurance, and empathy are the most dominant influence on customer satisfaction is empathy. The test results coefficient determinant is known that the variable quality of service and product quality can explain variation of 56.2% for customer satisfaction BPR BKK Jepara, while the remaining 43.8% is influenced by other variables not included in this study.Key words: Quality of Service, Quality Products and Customer Satisfaction.